Functional mapping of Toll/interleukin-1 signalling networks by expression cloning. (26th October 2005) - Kiss-Toth, E.; Wyllie, D.H.; Holland, K.; Marsden, L.; Jozsa, V.; Oxley, K.M.; Polgar, T.; Qwarnstrom, E.E.; Dower, S.K.
Abstract : Multiple cellular proteins have been identified as participating in Toll/interleukin-1 receptor-mediated inflammatory gene expression. The continuing isolation of novel components, based on sequence similarities, protein–protein interactions and protein purification, suggests that many elements of this signalling network remain to be identified. We report here the development of a high-throughput functional screening platform and its application for the identification of components of inflammatory signalling networks. Our results enable us to estimate that 100–150 gene products are involved in controlling the transcription of the human interleukin 8 gene. The approach, which is simple and robust, constitutes a general method for mapping signal transduction systems and for rapid isolation of a large number of signalling components based on the control of pathways leading to regulation of gene expression.